Impact of Teacher’s Islamic Self-Efficacy on the Effectiveness Formal and Informal Learning: An Analysis of Work Ethic and Classroom Management at Al Falah Darmo Senior High School: English - Hidayat, Ahmad Agus; Al Faruq, Abdul Qudus; Salsabilla, Selena Chayka (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
Educational effectiveness is often associated with technological integration, while the human aspect of education, particularly teacher Islamic self-efficacy, receives less attention. This study examines the influence of teacher self-efficacy on the effectiveness of formal and informal learning through work ethic and classroom management at IIBS SMA Al Falah Darmo Surabaya. Using a qualitative approach, data were collected through observations, interviews, and documentation, and analyzed descriptively. The findings indicate that teachers with strong Islamic self-efficacy demonstrate high work ethics, including discipline, effective time management, continuous professional development, and emotional regulation. Teacher self-efficacy also enhances classroom management through structured supervision and the integration of formal and informal learning. These practices positively affect student discipline, responsibility, and learning effectiveness. The study concludes that teacher Islamic self-efficacy is essential for achieving effective and sustainable learning outcomes alongside technological development Keywords: Teacher, Islamic Self-Efficacy, Learning Effectiveness, Work Ethic, Classroom Management.